Thermodynamic Studies of Solutions of Some Alkanes Solutes on Two Monomeric Liquid Crystals Stationary Phases - BENALIA, M.; BADJAH-HADJ-AHMED, A.Y.; DJEDID, M.; MEKLATI, B.Y.; AL-DUJAILI, A.H. (Asian Journal of Chemistry, 2010)
5-[4-(p-methoxyphenyl)-azophenyl]-2-butylthio-1,3,4-oxadiazole and 5-(4-(p-propoxyphenyl)-azophenyl)-2-butylthio-1,3,4-oxadiazole were used in gas chromatography at different temperatures to study the interactions and elution characteristics of some n-alkanes. These two liquid crystals contain the same backbone and differ in the partial replacement of the terminal alkoxy chain. The curve of the parameter ‘b’ in function of inverse absolute temperature shows breaks on the levels of the transition temperatures determined by DSC. Thermodynamic quantities show that these values depend to the number of alkanes carbons in these two phases liquid crystalline compounds. The transition temperatures obtained by gas chromatography are in good agreement with those found by DSC. The results are interpreted in terms of parameters ‘b’ and related thermodynamic quantities.